Settlement and Community Interrelations of Fouling Organisms in Cochin Harbour, India - B., Meenakumari; N., Balakrishnan Nair (Fishery Technology, 2025)
A qualitative and quantitative assessment of the fouling community on a sequential, progressive and cumulative basis carried out at the Cochin Harbour is presented in this paper. A total of 67 species were recorded in this study. The index of dominance of various animals was found. Mud-tube worms dominated during the pre-monsoon, cirripedes duringmonsoon and post-monsoon period. A comparison is attempted on the number of micro and macro foulers recorded from various Indian and world harbours. In India, Cochin ranks second in so far as the occurrence ofmacrofoulers are concerned. The correlation coefficient of the settled organisms was found and the modulus values are presented in the form of a matrix diagram. To separate out the groups of foulers with higher correlation coefficient, a dendrogram was constructed using correlation matrices and based on the clustering of animal groups.